A VANET-Based A* Route Planning Algorithm for Travelling Time- and Energy-Efficient GPS Navigation App. (18th July 2013) - Chang, Ing-Chau; Tai, Hung-Ta; Yeh, Feng-Han; Hsieh, Dung-Lin; Chang, Siao-Hui
Abstract : Most current navigation devices or apps, based on the global positioning system (GPS), only adopt static information for route planning. Although some are equipped with an RDS-TMC receiver to receive real-time traffic events, many of these real-time traffic events are irrelevant to the vehicle. This paper offers three major contributions. First, a vehicular-ad-hoc-network- (VANET-) based A * (V B A * ) route planning algorithm is proposed to calculate the route with the shortest travelling time or the lowest fuel consumption, depending on two real-time traffic information sources, which have not been used in traditional GPS navigation applications. The first traffic information source is the recorded traffic information of the road segment that the vehicle has passed through. It is further exchanged between vehicles through an IEEE 802.11p wireless link. The second traffic information is provided by Google Maps. A GPS navigation app is then implemented on the Android platform to realize V B A * . Finally, simulations for six route planning algorithms are executed by VANET simulator The ONE, in one congested and one noncongested time period, respectively. In summary, V B A * achieves significant reductions in both the average travelling time and fuel consumption of the planned route, as compared to traditional route planning algorithms.